IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TO IMPROVE STUDENT COOPERATION IN CLASS - Shafira Setia Putri Shafira (CV Grasta Glory, 2026)
The implementation of the cooperative learning model is one effort that can be made to increase student activity and cooperation in the learning process. This model emphasises group learning activities where students collaborate, discuss, and help each other understand the subject matter. This article aims to explain the application of cooperative learning in learning, including its definition, basic principles, characteristics, and application in teaching and learning activities. The method used in this paper is a literature review by reviewing various books and journals related to cooperative learning. The results show that the implementation of cooperative learning can improve social interaction, communication skills, and student responsibility in completing group assignments. Furthermore, learning becomes more active and enjoyable because students are directly involved in group discussions and collaboration. Thus, cooperative learning can be an effective learning model for creating a more active and collaborative learning process and supporting the development of students’ social skills.